Unintentional Infusion of Phenylephrine into the Epidural Space. Issue 5 (1st March 2016) - Townley, Kress R.; Lane, Jason; Packer, Robyn; Gupta, Rajnish K.
Abstract : We describe a patient who received an unintentionally prolonged epidural infusion of phenylephrine. The patient experienced no major morbidity. However, this case highlights the continuing problem of wrong-route drug administration and the urgent need to adopt route-specific connections.